Broken Femoral Intramedullary Locking Nails with Nonunion: A difficult combination! - DC, Gopal Sagar; Gurung, Sandeep (Journal of Nepalgunj Medical College, 2018)
Background: The diaphyseal fracture of femur is universally treated with intramedullary interlocking nails. Non-union with properly done interlocking nail is not very common. When broken nail and non-union coexist, it becomes a real challenge. We reviewed our isolated femoral shaft fractures treated with antegrade interlocking nails that presented with broken nails, bolts and non-union. We discuss our simple technique of retrieval of broken nail units, their management and results with revision nailing.Materials and methods: We reviewed our cases of femoral intramedullary locking nails operated from 2012 November to 2017 November and observed that, out of 197 cases; Eight cases of broken nails were managed in our center Nepalgunj medical college Nepalgunj. Patients were operated in lateral position under combined spinal epidural anaesthesia. We removed the broken nail segment with our simple yet less destructive technique and revised with bigger nails.Results: Out of 197 cases of fracture shaft femur treated with IM nail, 8 cases were found to have broken nails. Seven cases were associated with non-union of femur. In one case, the femur united in spite of broken nail. In all the cases broken nail were removed in a similar manner and was struggle free. Exchange nailing was done in seven cases and only one case was augmented with bone graft from ipsilateral iliac crest. Union was achieved in all seven cases.Conclusion: IMIL nail is the well-established, minimally invasive osteosynthesis for long bones fracture. Nonunion and broken implant when coexist the management becomes difficult.